Comparative genomics and biocontrol potential of five Bacillus strains isolated from grapevine rhizosphere - Lajoinie, Denise M. (2026)
Fungal diseases such as Botrytis cinerea threaten grapevine production, causing substantial yield losses and quality deterioration. To manage these pathogens, viticulture relies heavily on chemical fungicides, which may negatively affect the environment, human health, and wine quality. The growing demand for environmentally safe and residue-free alternatives has therefore stimulated interest in Bacillus spp. as biological control agents. In this study, five Bacillus strains previously isolated from the rhizosphere of Argentine vineyards and known to exhibit biocontrol activity against B. cinerea were investigated to determine their taxonomic identity and biocontrol potential. Whole-genome sequencing and comparative genomic analyses revealed two clearly defined species groups: Bacillus cereus sensu stricto (FAU20, AMCV8, and TCT6) and Bacillus subtilis sensu stricto (AMCV2 and FAU18). The classification of B. cereus group strains remained challenging due to high genomic similarity and inconsistencies among current taxonomic frameworks. Genome mining identified multiple biosynthetic gene clusters associated with secondary metabolite production, including cyclic lipopeptides. Bioassays confirmed that AMCV2 and FAU18 produced cyclic lipopeptides capable of inhibiting B. cinerea, whereas the B. cereus group strains produced only siderophores. Overall, these findings support AMCV2 and FAU18 as promising candidates for sustainable Bacillus-based biofungicides.